2020
DOI: 10.1111/jcpe.13297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self‐performed mechanical plaque control frequency on gingival health in subjects with a history of periodontitis: A Randomized Clinical Trial

Abstract: Aim This randomized clinical trial evaluated the effect of the frequency of self‐performed mechanical plaque control (SPC) on gingival health in subjects with a history of periodontitis. Materials and Methods Forty‐two subjects participating in a routine periodontal maintenance program were randomized to perform SPC at 12‐, 24‐ or 48‐hr intervals. Plaque index (PlI) and gingival index (GI) were evaluated at baseline, and days 15, 30 and 90 of study. Probing depths, clinical attachment levels and bleeding on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The data that support the findings of this study are openly available in Medline [http://www.pubmed.com] at https://doi.org/10.1111/jcpe.13297, Maier et al, 2020.…”
Section: Data Availability Statementsupporting
confidence: 75%
See 4 more Smart Citations
“…The data that support the findings of this study are openly available in Medline [http://www.pubmed.com] at https://doi.org/10.1111/jcpe.13297, Maier et al, 2020.…”
Section: Data Availability Statementsupporting
confidence: 75%
“…In our previous study (Maier et al, 2020), pOH intervals of 12 and 24 h demonstrated the same pattern of dental plaque accumulation and gingival inflammation. Thus, in the present study, we collapsed them into one group (G12/24) to compare with the group that performed pOH every 48 h (G48).…”
Section: Methodssupporting
confidence: 60%
See 3 more Smart Citations